Service-oriented process control using high-level Petri Nets - João Marco de Melo Pereira Mendes (2008)
Service-oriented systems constitute a suitable approach for the development of modular, flexible and reconfigurable production systems, addressing the current requirements imposed by global markets. This paper focuses on the process control of Service-oriented production systems, whose behavior is regulated by the coordination of services that are available from distributed modular and collaborative control components. The proposed control is based on a kind of Highlevel Petri Nets tailored for the description, connection and synchronization of different concurrent processes. Several features can be distinguished by this approach, since its modularity, control reusability, flexibility and other valuable inherited characteristics from the proposed High-Level Petri Nets.